2017
DOI: 10.1002/smr.1891
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing key success factors of software projects using fuzzy AHP

Abstract: The main purpose of most software projects is to build an effective and efficient product that satisfies the user's requirements under constraints of basic available resources. Thus, recognizing the critical features that may affect developing the application could be imperative. In this study, we apply the fuzzy analytic hierarchy process (AHP) to the issue of ordering key success factors (KSFs) for software development projects. To do this, we first simplified the constrained fuzzy AHP method, and then from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 43 publications
0
70
0
2
Order By: Relevance
“…In this study, the findings of the literature review were unable to explain the generalizability of the results because of the limited responses obtained from the experts and because most of them were collected from the software industries located in India. However, on the basis of the outcomes of various studies similar in nature to that of our study, the authors firmly believe that the sample size was sufficiently large to explain the generalizability of this study.…”
Section: Threats To Validitymentioning
confidence: 99%
“…In this study, the findings of the literature review were unable to explain the generalizability of the results because of the limited responses obtained from the experts and because most of them were collected from the software industries located in India. However, on the basis of the outcomes of various studies similar in nature to that of our study, the authors firmly believe that the sample size was sufficiently large to explain the generalizability of this study.…”
Section: Threats To Validitymentioning
confidence: 99%
“…A fuzzy AHP method is selected as a factor-weighting model because studies have declared its effectiveness in prioritizing and ranking of factors, criteria, alternatives in construction management, and other various disciplines [42][43][44][45][46][47][48][49][50]. Fuzzy AHP can be applied in several ways.…”
Section: Fuzzy Ahp Methodmentioning
confidence: 99%
“…A review by [24] showed an increased focus on human actors, project management alternative acceptance, adapt to change. The work uses a fuzzy approach to order key success factors of projects [4].…”
Section: Related Workmentioning
confidence: 99%
“…Project and portfolio managers must harvest the features of project portfolio management (PPM) software to ensure proper control. Common issues of PPM include prioritization [4], inaccurate reporting, resource utilization, and software development lifecycle. The primary objective of PPM is to execute projects that support strategic organization goals under constraints of scope, time and resources.…”
Section: Introductionmentioning
confidence: 99%